Sculpture of Kartikeya on the Shikhara of the Rangamandapa - Temples of India Project Team (Jio Institute, 2024)
A beautiful sculpture of Kartikeya can be seen on the western pediment of the shikhara (superstructure) of the rangamandapa (open type of pillared hall). The God of war is depicted seated, with four faces, three of which are visible in the sculpture. He has eight arms and holds his weapons including a shakti/vel (spear), arrow, and bow. He is holding a cork in one of his hands and his frontal hands are carrying an akshamala (rosary) and a kamandalu (water pot). The slender body of the young war God is adorned with jewellery and yajnopavita (sacred thread). It is one of the most beautiful representations of Kartikey.